Estiércol de Ovino y Fertilización npk en la acumulación de materia seca en hordeum vulgare l. var. Zapata en un Suelo Ácido de Santiago de Chuco, La Libertad - Alcántara Ríos, Glenn Marcos (2017)
Was evaluated potted effect of sheep manure and NPK fertilization on the accumulation of matter dry Hordeum vulgare L. Var Zapata in a soil with a pH of 4.1 and 8.6 cmol (+).Kg soil-1 of exchangeable acidity, located in the town of Alto Paraiso in the province of Santiago de Chuco, La Libertad, using a design randomized complete block with four replications. The treatments were two levels of sheep manure (0 and 8g.kg soil-1) and 3 levels of NPK fertilizer (40-40-40, 80-80-80 and 120-120-120 mg / kg soil of N, P2O5 and K2O). Were evaluated, grain dry matter, aerial parts,root,total, number of tillers and plant height .The results of the ANOVA and test Tukey (5%) showed that sheep manure and the level of 120-120-120 NPK fertilizer increased the accumulation of total dry matter and the number of tillers for independently. Further the doses 80-80-80 increases the dry matter the roots and sheep manure increases the dry matter of grain and aereal. The treatments did not affect plant height.